2006
DOI: 10.1242/jeb.02045
|View full text |Cite
|
Sign up to set email alerts
|

Differential effects of experimental and cold-induced hyperthyroidism on factors inducing rat liver oxidative damage

Abstract: SUMMARY Thyroid hormone-induced increase in metabolic rates is often associated with increased oxidative stress. The aim of the present study was to investigate the contribution of iodothyronines to liver oxidative stress in the functional hyperthyroidism elicited by cold, using as models cold-exposed and 3,5,3′-triiodothyronine (T3)- or thyroxine(T4)-treated rats. The hyperthyroid state was always associated with increases in both oxidative capacity and oxidative damage of the tissue. The most … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

5
47
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 47 publications
(52 citation statements)
references
References 35 publications
5
47
0
Order By: Relevance
“…Conversely, other factors, exhibiting different serum concentrations in functional and experimental hyperthyroidism, should be involved in mitochondrial proliferation associated to cold exposure. Unlike cold exposure, T 3 administration strongly decreases serum levels of T 4 , (Venditti et al, 2006a), which has been reported to have intrinsic biological activity in the cold (Cageao et al, 1992). Plasma levels of catecholamines, which are not modified in altered thyroid states (Stoffer et al, 1973), remarkably increase during cold exposure (Storm et al, 1981).…”
Section: Introductionmentioning
confidence: 96%
See 3 more Smart Citations
“…Conversely, other factors, exhibiting different serum concentrations in functional and experimental hyperthyroidism, should be involved in mitochondrial proliferation associated to cold exposure. Unlike cold exposure, T 3 administration strongly decreases serum levels of T 4 , (Venditti et al, 2006a), which has been reported to have intrinsic biological activity in the cold (Cageao et al, 1992). Plasma levels of catecholamines, which are not modified in altered thyroid states (Stoffer et al, 1973), remarkably increase during cold exposure (Storm et al, 1981).…”
Section: Introductionmentioning
confidence: 96%
“…Thus, long-term effects of thyroid hormones or states modulating thyroid gland activity, such as cold exposure, are believed to be transduced through T 3 -induced changes in both nuclear and mitochondrial gene expression. In liver from both T 3 -treated (Fernández et al, 1985;Seitz et al, 1985;Venditti et al, 2006a) and cold-exposed animals (Guernsey and Stevens, 1977;Shiota et al, 1985;Venditti et al, 2004) such changes lead to enhanced tissue O 2 consumption. However, in experimental hyperthyroidism the increase in liver respiration involves increases in the amount of respiratory chain proteins and inner surface area (Jacovcic et al, 1978) of mitochondria without changes in their number (Goglia et al, 1989) and protein mass (Venditti, et al, 2006a).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Cases have been reported to occur with and without heart failure, although cholestasis is usually more severe in cases with concurrent heart failure 5. There is evidence of a mechanism involving mitochondrial‐induced apoptosis, another theory cites evidence that oxidative stress from a hyperthyroid state as a cause of hepatotoxicity and cholestasis 7. To date, there is no strong evidence to suggest that thyroid hormone is directly toxic to the liver 8.…”
Section: Discussionmentioning
confidence: 99%